2021
DOI: 10.3390/diagnostics11101781
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death in Systemic Sclerosis: Diagnostics to Assess Risk and Inform Management

Abstract: Cardiac disease is a leading cause of death in systemic sclerosis (SSc) and sudden cardiac death (SCD) is thought to occur more commonly in SSc than in the general population. Diffuse myocardial fibrosis, myocarditis and ischaemic heart disease are all prevalent in SSc and can be reasonably hypothesised to contribute to an increased risk of SCD. Despite this, SCD remains a relatively understudied area of SSc with little understood about SSc-specific risk factors and opportunities for primary prevention. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 89 publications
1
2
0
Order By: Relevance
“…In our study, we found that male gender is associated with a severe course of SSc with cardiac involvement, which is consistent with previous studies [11]. We also found that a risk factor for heart involvement is extensive skin sclerosis expressed as high values of mRSS.…”
Section: Risk Factors Of Cardiac Involvement In Systemic Sclerosissupporting
confidence: 93%
“…In our study, we found that male gender is associated with a severe course of SSc with cardiac involvement, which is consistent with previous studies [11]. We also found that a risk factor for heart involvement is extensive skin sclerosis expressed as high values of mRSS.…”
Section: Risk Factors Of Cardiac Involvement In Systemic Sclerosissupporting
confidence: 93%
“…In 50% of cases, cardiac arrest is the first manifestation of SCD [ 3 ], and the survival rate is very low. Only 10% of patients with cardiac arrest can survive to discharge [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arrhythmias and conduction abnormalities worsen the overall prognosis of SSc. These abnormalities may apparently be mild but can lead to a fatal outcome like sudden cardiac death in SSc ( Ross et al, 2021 ). Although myocardial damage and fibrosis are clearly important factors leading to conduction abnormalities, the underlying arrhythmogenic mechanisms observed in SSc are not well understood, and the activity of cardiac ion channels responsible for the cardiac myocyte action potential have not been investigated in the context of SSc with cardiac involvement.…”
Section: Introductionmentioning
confidence: 99%